Pembuatan Infusa Daun Seledri sebagai Obat Antihipertensi dan Pemeriksaan Kadar Glukosa Darah dan Kolesterol pada Masyarakat Desa Tengah Kecamatan Pancurbatu - Antetti Tampubolon; Jhonson P Sihombing (Jurnal Abdi Masyarakat Kita, 2022)
Many people use traditional medicine which is part of Indonesia's natural wealth. The use of traditional medicine has long been carried out since ancient times. Traditional medicine is widely used for the treatment of hypertension, cholesterol, antidiabetic, cancer, diarrhea and so on. One of the traditional medicines that is often used in the community is celery leaf which is efficacious as antihypertensive and cholesterol-lowering. The purpose of this community service is for participants to know how to make celery leaf infusion in accordance with the requirements for making infusions, to know the profile of blood sugar, cholesterol levels and to educate the public by providing counseling about hypertension, cholesterol and family medicinal plants to the people of Tengah Village, Pancur Batu District. The method used is by distributing questionnaires before and after counseling to determine the level of public knowledge about hypertension, diabetes, cholesterol, family medicinal plants and how to make infusions. Of the 20 participants who were checked for blood sugar (KGD) and cholesterol levels, the results obtained: 4 participants had normal fasting blood sugar levels, 9 participants had prediabetes, 7 participants had diabetes, 7 participants had normal blood cholesterol, 9 participants had blood cholesterol at the limit. 4 participants had high blood cholesterol. The level of public knowledge about hypertension, diabetes, cholesterol, family medicinal plants and making infusions before counseling was done was quite good with a score of 60.71% and after counseling was good with a score of 92.85% It can be concluded that 20% of participants had normal KGD, 45% prediabetes, 35% diabetes, 35% of participants had normal blood cholesterol, 45% had high cholesterol, 20% had high blood cholesterol and the level of public knowledge increased from good enough to good after counseling.